PENGARUH PROFITABILITAS, LIKUIDITAS, DAN UKURAN PERUSAHAAN TERHADAP NILAI PERUSAHAAN DENGAN STRUKTUR MODAL SEBAGAI VARIABEL MODERASI - Kangga, Doris Ratnasari; Suwandhy, Emily; Lee, Mirelline Valencia (Jurnal Ilmiah Mahasiswa Ekonomi Akuntansi, 2025)
This study aims to examine and analyze the influence of profitability, liquidity, and company size on firm value, with capital structure as a moderating variable, in Consumer Non-Cyclicals companies listed on the Indonesia Stock Exchange for the period 20212023. The population of this study consisted of 122 Consumer Non-Cyclicals companies listed during that period. From this population, a sample of 57 companies was selected using the purposive sampling method. The data analysis method used in this study is Partial Least Squares (PLS) with a two-stage approach model, consisting of an outer model test, a model feasibility test, and an inner model test, using the SmartPLS version 3.2.9 program. The results of the study show that profitability has a positive effect on firm value, while liquidity has a negative effect on firm value. Meanwhile, firm Size and capital structure do not have an effect on firm value. Furthermore, Capital Structure moderates the relationship between profitability and liquidity with firm value, but does not moderate the relationship between firm size and firm value.